Examining the factor structure of the Physical Literacy for Life self-assessment tool (PL4L) among Japanese adults and its relationship with the stages of change model for participation in regular physical activity - Matsunaga, Misaki; Suzuki, Koya; Matsui, Masahiro; Toyama, Kenta; Ito, Shizuo; Okade, Yoshinori; Kasuga, Kosho; Deng, Pengyu; Matsuo, Tetsuya; Morioka, Yasunori; Aono, Hiroshi; Naito, Hisashi (Frontiers in Public Health, 2025)
IntroductionPhysical literacy contributes to physical activity and comprises four conceptually interrelated domains: physical, emotional, social, and cognitive. The International Sport and Culture Association proposed the Physical Literacy for Life self-assessment tool (PL4L); however, its factor structure and usability are not clear. This study aimed to examine the factor structure and internal consistency of the PL4L in adults and its association with the stages of change model for participation in regular physical activity.MethodsFor this study, a total of 940 Japanese adults (age: 41.8 ± 13.2 years) completed a web-based cross-sectional survey. Physical literacy (PL) was assessed using the PL4L. The stages of change model regarding participation in regular physical activity were examined using a self-reported questionnaire that applied the Transtheoretical Model. Internal consistency was assessed by Cronbach’s α and McDonald’s ω. Factor structure was evaluated using confirmatory factor analysis. Structural equation modeling was used to investigate the relationship between the PL4L and the stages of change for participation in regular physical activity. Internal consistency coefficients were found to be high.ResultsIn the confirmatory factor analysis, the modified model, incorporating theoretically justified error covariances, demonstrated a good fit. The factor loadings between domains and items were all significant. Significant associations were also identified between PL and stages of change for participation in regular physical activity.DiscussionThe PL4L’s factor structure is consistent with the concept of physical literacy among Japanese adults, which correlates with the stages of change for participation in regular physical activity. Future studies should investigate whether addressing PL can effectively increase physical activity levels.